Postoperative fever after elective minimally invasive resection for gastric and colorectal cancer: incidence, risk factors and characteristics - He, Fan; Tang, Chenglin; Yang, Fuyu; Zhao, Dongqin; Xiong, Junjie; Zou, Yu; Chen, Defei; Huang, Guoquan; Qian, Kun (Frontiers in Oncology, 2025)
PurposeTo analyze the incidence and risk factors of postoperative fever (POF) in gastrointestinal cancer (GIC), discuss the influence of POF on short-term clinical outcomes, and predict anastomotic leakage (AL) based on POF characteristics.MethodsOverall, 1362 patients that underwent radical resection for GIC were retrospectively analyzed. POF was defined as a postoperative temperature ≥38°C during hospitalization. Patients were divided according to whether they experienced POF. The influence of POF on short-term clinical outcomes was analyzed using propensity score matching. A subgroup analysis was conducted to examine the relationship between different POF characteristics and AL or infection-related complications.ResultsPOF occurred in 172 patients (12.6%). Overall, 115 patients (66.9%) had fever ≥38.6°C, while 105 (61.0%) had fever at postoperative day (POD) 2, and 73 (42.4%) had POF multiple times. Multivariate analysis showed that patients with a preoperative albumin level < 37 g/L (odds ratio [OR]=1.57, p=0.016), operative time >195min (OR=1.55, p=0.020), and radical gastrectomy (OR=1.84, p=0.009) were more likely to develop POF. Compared to patients without fever, drainage tube indwelling time, duration of antibiotic use, and hospital stay were prolonged, while AL and infection-related complications were more common in patients with POF. POF ≥38.6°C (OR=1.74, p=0.039) and PCT >0.7 ng/mL (OR=2.99, p=0.022) at POD 3 were early predictors of AL.ConclusionPOF was closely related to preoperative albumin levels, operative time, and type of operation, and it delayed postoperative recovery in patients with GIC. And POF ≥38.6°C and PCT >0.7 ng/mL at POD 3 were independent predictors of AL.